Utilizing syllabi to support access services and beyond: A case study. Issue 1 (2nd January 2017) - Parrott, Justin; Lindsay, Beth Daniel
ABSTRACT: New York University Abu Dhabi (NYUAD) Library receives copies of all course syllabi to provide a number of services to faculty and students related to acquisitions, access, collection development, subject liaison, and library instruction. Access services and acquisitions staff, as well as subject liaison librarians, work together using specific workflows to ensure that subject-relevant materials are selected and purchased on an ongoing basis and access needs are met by course reserves or the learning management system. Additionally, the library works closely with the NYUAD Bookstore, which also receives textbook orders, to ensure that students have access to all required and supplementary materials on the first day of classes.